The state of renal sympathetic denervation for the management of patients with hypertension: A systematic review and meta‐analysis. Issue 4 (12th November 2020) - Syed, Moinuddin; Osman, Mohammed; Alhamoud, Hani; Saleem, Maryam; Munir, Muhamad Bilal; Kheiri, Babikir; Balla, Sudarshan; Kawsara, Akram; Daggubati, Ramesh
Abstract: Background: Sympathetic nervous system plays a central role in the development and persistence of essential hypertension. In recent years renal sympathetic denervation (RSD) has emerged as a promising option for the treatment of patients with hypertension. Methods: We conducted a literature search of PubMed, EMBASE, Cochrane library and Clinicaltrials.gov from inception through April 20, 2020. Outcomes of interest were change in 24‐hour ambulatory systolic (ASBP) or diastolic blood pressure (ADBP) and change in office systolic (OSBP) or diastolic blood pressure (ODBP). We pooled data from randomized controlled trials (RCTS) comparing RSD to sham procedures in the management of hypertension using the random effect model. Results: A total of 1, 363 patients from eight studies were included in the current meta‐analysis. The mean age of the included patients was 56 ± 2.6 years, 29% were women and the median duration of maximum follow up was 6‐month (range 3–12 month). There was more reduction favoring RSD in ASBP (Weighted mean difference [WMD] ‐3.55; 95% CI ‐4.91 – −2.19, p  < .001, I 2 = 0%), ADBP (WMD ‐1.87; 95% CI ‐3.07 – −0.66, p = .002, I 2 = 43%), OSBP (WMD ‐5.5; 95% CI ‐7.59 – −3.40, p  < .001, I 2 = 7%) and ODBP (WMD ‐3.20; 95% CI ‐4.47 – −1.94, p  < .001, I 2 = 14%). Conclusion: The use of RSD for the management of hypertension resulted in effective reduction in the ambulatory and office blood pressure compared to sham procedure. Adequately powered RCTs of RSD are needed to confirm safety, reproducibility and assess the impact on clinical outcomes.